Bedouin Weaving of Saudi Arabia and its neighbours - Hilden, Joy Totah (Saudi Arabia; Al-Turath, 2010)
Bedouin women were expected to master the art of making entire tents as well as a wide range of rugs, saddlebags and other equipment able to withstand the rigours of the desert. They took a fierce pride in their work and produced, on the simplest ground looms, textiles that were at once hard-wearing and of vibrant aesthetic appeal. The true craftspeople of the desert. Bedouin women wove to provide the very fabric of day-to-day living. In doing so they adorned their lifestyle with shape and colour and contributed an essential element to the image of the desert tribes. Joy Hilden describes the weaving techniques of the Bedouin in the context of their transitional mode of life, as they adapt from their centuries-old nomadic existence to being both semi- and fully settled. She gathered her information on dyeing, spinning and weaving while living and travelling in Saudi Arabia between 1982 and 1994, extending her scope with trips to other parts of the Arabian Peninsula and adjacent Arab countries. She describes visits to Bedouin families, desert markets and urban centres where Bedouin gathered. Her work comes at a time when many tribal peoples are losing their cultural traditions and, with them, their crafts and the material of everyday life in the desert. This is the most exhaustive study to date of the weaving methods practised by the Bedouin of Saudi Arabia. Profusely illustrated, and giving thorough instruction in techniques, Bedouin Weaving is an essential companion for collectors and connoisseurs of flat-weave textiles, the category into which Bedouin weavings fall. It is aimed both at general readers and at weavers, craftspeople in general, students, ethnographers, and museum and textile authorities
PORTABLE AND PRACTICAL, as well as tough and colourful, Bedouin textiles played until recent times a vital and functional part in the life of the Arab nomads.
English
Keywords: GR420-426 Folklore- By Subject- Costume, jewelry; Bedouins; Textiles; Weaving